2017
DOI: 10.12669/pjms.332.11757
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyle behavior of employees in small and medium-sized enterprises in Aydin, Turkey

Abstract: Objective:To determine healthy lifestyle behavior and affecting risk factors in workers at small and medium-sized enterprises from four different sectors in Aydin, Turkey.Methods:This cross-sectional study was conducted at four different small and medium-sized enterprises in Aydin, Turkey and 264 employees participated in the study. A questionnaire was used for data collection. It consisted of questions about socio-demographic features (age, gender, marital status, education, perceived income, occupation and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
2
2
0
7
Order By: Relevance
“…In addition to attitude, this study found that female residents may adopt more health promotion lifestyle, corroborating several studies [37,38]. The effects of education and family income on health behavior are similar to previous studies [39,40].…”
Section: Discussionsupporting
confidence: 91%
“…In addition to attitude, this study found that female residents may adopt more health promotion lifestyle, corroborating several studies [37,38]. The effects of education and family income on health behavior are similar to previous studies [39,40].…”
Section: Discussionsupporting
confidence: 91%
“…Benzer biçimde Aydın ve İzmir'de yapılan çalışmalarda yaş artışı ile birlikte sağlık sorumluluğu, egzersiz ve beslenme faktörü puanlarında artış olduğu belirtilmiştir. 16,17 Yaş artışının deneyim, algı artışı, kronik hastalık varlığı gibi pek çok faktör üzerinden bir etki gerçekleştirme olasılığı yüksektir. Ancak, her araştırmada da yaş faktörünün belirleyici etkisi gözlenmemektedir.…”
Section: Introductionunclassified
“…Literatüre bakıldığında, yaş kimi çalışmalarda anlamlı bir fark oluşturmazken, 13 kimi çalışmalarda ise ileri yaş grubunda SYBDÖ puanı anlamlı olarak yüksektir. 6,12,14 Bu farklılık, araştırma gruplarının yaş yapısının farklılığından, yaş arttıkça kronik hastalıklara bağlı olarak da bireylerin sağlıklı yaşam biçimi davranışlarına yöneliyor olmalarından kaynaklanabilir. Cinsiyet, bizim araştırmamızda anlamlı bir fark oluşturmayıp, benzer şekilde literatürdeki çalışmalarda da cinsiyete göre anlamlı fark saptanmamıştır.…”
Section: Introductionunclassified
“…Araştırma grubunda medeni durum SYBDÖ puanının literatüre benzer biçimde medeni durumun etkisinin olmadığı bulunmuştur. 8,[12][13][14][15] Çalışmamızda, Konya'da yürütülen bir çalışmaya benzer biçimde, yalnız başına yaşayanlarda SYBDÖ puanı anlamlı olarak yüksek bulunmuştur. 6 Araştırmada, sağlık güvencesi olma durumuna göre İran'da yürütülen bir çalışmayla benzer biçimde, ölçek puanları arasında anlamlı fark yokken, bazı çalışmalarda da sağlık güvencesi olanlarda SYBDÖ puanı anlamlı olarak yüksek bulunmuştur.…”
Section: Introductionunclassified
See 1 more Smart Citation